Midpalatal suture maturation: Classification method for individual assessment before rapid maxillary expansion - Angelieri, Fernanda; Cevidanes, Lucia H. S.; Franchi, Lorenzo; Gonçalves, João Roberto [UNESP]; Benavides, Erika; McNamara, James A. (Elsevier B.V., 2013)
Introduction: In this study, we present a novel classification method for individual assessment of midpalatal suture morphology. Methods: Cone-beam computed tomography images from 140 subjects (ages, 5.6-58.4 years) were examined to define the radiographic stages of midpalatal suture maturation. Five stages of maturation of the midpalatal suture were identified and defined: stage A, straight high-density sutural line, with no or little interdigitation; stage B, scalloped appearance of the high-density sutural line; stage C, 2 parallel, scalloped, high-density lines that were close to each other, separated in some areas by small low-density spaces; stage D, fusion completed in the palatine bone, with no evidence of a suture; and stage E, fusion anteriorly in the maxilla. Intraexaminer and interexaminer agreements were evaluated by weighted kappa tests. Results: Stages A and B typically were observed up to 13 years of age, whereas stage C was noted primarily from 11 to 17 years but occasionally in younger and older age groups. Fusion of the palatine (stage D) and maxillary (stage E) regions of the midpalatal suture was completed after 11 years only in girls. From 14 to 17 years, 3 of 13 (23%) boys showed fusion only in the palatine bone (stage D). Conclusions: This new classification method has the potential to avoid the side effects of rapid maxillary expansion failure or unnecessary surgically assisted rapid maxillary expansion for late adolescents and young adults.